Living Donation Has a Greater Impact on Renal Allograft Survival Than HLA Matching in Pediatric Renal Transplant Recipients. Issue 12 (December 2016) - Marlais, Matko; Hudson, Alex; Pankhurst, Laura; Fuggle, Susan V.; Marks, Stephen D.
Abstract : Background: Living donor (LD) kidney transplantation accounts for around half of all pediatric renal transplant recipients and results in improved renal allograft survival. The aim of this study was to determine the effect of HLA matching on deceased and LD renal allograft outcomes in pediatric recipients. Methods: Data were obtained from the UK Transplant Registry held by NHS Blood and Transplant on all children who received a donation after brain death (DBD) or LD kidney-only transplant between 2000 and 2011. HLA-A, HLA-B and HLA-DR mismatches were categorized into 4 levels and 2 groups. Data were fully anonymized. Results: One thousand three hundred seventy-eight pediatric renal transplant recipients were analyzed; 804 (58%) received a DBD donor kidney, 574 (42%) received an LD kidney. Five-year renal allograft survival was superior for children receiving a poorly HLA-matched LD kidney transplant (88%, 95% confidence interval [95% CI], 84-91%) compared with children receiving a well HLA-matched DBD kidney transplant (83%, 95% CI, 80-86%, log rank test P = 0.03). Five-year renal allograft survival was superior for children receiving an LD kidney with 1 or 2 HLA-DR mismatches (88%, 95% CI, 84-91%) compared with children receiving a DBD kidney with 0 HLA-DR mismatches (83%, 95% CI, 80-86%, log rank test P = 0.03). Conclusions: In children, poorly HLA-matched LD renal transplant outcomes are not inferior when compared with well HLA-matched DBD renal transplants. It is difficult to justify preferentially waiting for an improved HLA-matched DBD kidney when a poorer HLA-matched LD kidney transplant is available. Abstract : This registry analysis involving 1, 378 pediatric renal transplant recipients shows similar 5-year outcomes comparing poorly HLA matched living with well HLA matched deceased donor renal transplants, questioning current allocation algorithms and increasing the debate around waiting time versus risk of sensitization.